Ground water quality in Ciracas sub-district, East Jakarta, Indonesia - A. Alwin; Tri Cahyono; Ali Sya’ban; Siti Dahlia (Caspian Journal of Environmental Sciences)
The study aimed to know, and get a picture of the condition of groundwater quality in the area of Ciracas Urban Sub-District, Ciracas District, East Jakarta, Indonesia. Besides, to know the groundwater in the residential area of Ciracas Sub-district, East Jakarta has been contaminated or not based on Permenkes RI's clean water quality standard. No.416 / Menkes / per / IX / 1990. This is a descriptive study based on laboratory analyses. To determine groundwater samples in the study area, we used a sampling technique based on settlement density. The results of the study exhibited that the condition of ground water quality in the study area, according to the physical quality parameters, was odorless. Total dissolved solids (TDS) ranged from 489.1 mg L-1 to 298.2 mg L-1; turbidity ranged from 0.30 to 45.08 NTU. Unwelcome, temperature was 30 °C, color ranged between 4 and 13 TCU. Chemical quality of iron (Fe) ranged from 1600 MPN / 100 mL, while total bacterial coliform content was allowed at 50 MPN / 100 mL. This means that groundwater in Ciracas Urban Sub-District, Ciracas District, East Jakarta can not be used as a source of clean water.